Progressive degradation of acetylated wood by the brown rot fungi Coniophora puteana and Rhodonia placenta - Belt, Tiina; Awais, Muhammad (Springer Nature, 2025)
Acetylation is a wood modification method that reduces the hygroscopicity of wood and increases its resistance to degradation by wood decaying fungi. Even though acetylated wood can have very high decay resistance, the wood material can be degraded and sometimes deacetylated by fungi. This study investigated the degradation and deacetylation of acetylated wood by Coniophora puteana and Rhodonia placenta to better understand the relationship between degradation and deacetylation in two different brown rot fungi. Wood samples were exposed to the fungi in a stacked-sample decay test, followed by acetyl content measurements and FTIR spectroscopy to investigate chemical changes in the samples. The results showed that both fungi could degrade acetylated wood to high mass loss despite a strong reduction in moisture content, but only R. placenta was found to cause preferential deacetylation. The deacetylation was slight and only observed in the early stages of decay in highly acetylated wood. Otherwise, acetyl groups were lost from the samples at the rate of mass loss. FTIR spectroscopy confirmed the loss of acetyl groups and revealed some chemical differences between unacetylated and acetylated wood. The spectral data indicated the loss of acetyl groups from lignin, which suggests that the loss of acetyl groups is not only due to the degradation of acetylated carbohydrates. The degradation of acetylated wood required further investigation, but it is clear that extensive deacetylation is not a requirement for brown rot degradation.
Keywords: acetylation; wood degradation; brown rot fungi; deacetylation; FTIR spectroscopy